Development of Paklek Media on the Five Senses Material to Strengthen Student Learning Motivation in Elementary School - Putri, Sinta Kiswoyo; Thohir, Anas; Utama, Candra (Indonesian Journal of Primary Education, 2024)
The teaching-learning process is specifically designed for the benefit of students, with the aim of making them feel happy and motivated in learning. However, many teachers still struggle to enhance students' learning motivation, especially in the subject of science, specifically the five senses. This research aims to create a game-based learning media product considered valid by media and subject matter experts, practical for use by teachers and students, and effective in improving students' learning motivation. This research and development used the (RD) ADDIE model. The research results indicate that the PAKLEK media can be effectively applied in learning, as evidenced by validation results from subject matter and media experts averaging 88%, with a valid category. In the practicality test, the PAKLEK media obtained an average score of 94%, with a highly practical category, according to practitioners, namely users in small group trials and field trials. The practicality of the media obtained 96.5%, with a highly effective category. Additionally, the survey results on student motivation showed a significant increase, from 56% to 94%, indicating very high effectiveness. The N-Gain test also showed highly effective results, with a score of 0.87. Thus, it can be concluded that the PAKLEK media for the five senses subject is suitable for enhancing elementary school students' motivation